Sunfire Industrial SOC Stacks and Modules. (2nd June 2015) - Strohbach, Thomas; Mittmann, Frank; Walter, Christian; Schimanke, Danilo; Geipel, Christian
Abstract : In the past years, sunfire has increased its product portfolio and production depth. Four product classes (single stacks and stack modules for SOFC and SOEC) are tackling several markets (off-grid, on-grid, mobile). A ceramic center and a new production facility were inaugurated. The R&D activities are strongly driven by market requirements. With the new SOC stack electrolysis operation is introduced aside fuel cell operation. Furthermore, an increase in power density and a reduction of cost was achieved under the constraint of using standard industrial materials. Latest results of SOC single stack testing like I-V curves and reversible operation will be presented. The engineering and testing of stack modules in the power range >25kW will be also shown.